Special Issue on Astrophysics & Geophysics: Research and Applications - Vladimir A. Srećković; Aleksandra Nina (Data, 2019)
The earth’s layers and space are media permanently exposed to the influences of numerous perturbations characterized by time- and space-dependent intensity. For this reason, the detection of astrophysical and terrestrial events and their influences, as well as the development and application of various models, must be based on observational data. The aim of this Special Issue, “Astrophysics & Geophysics: Research and Applications„ in Data, is to engage a wide community of scientists to reorganize and expand current knowledge in this field. This Special Issue contains five articles, which include a wide range of topics such as big data in astrophysics and geophysics, data processing, visualization and acquisition, Earth observational data, remote sensing, etc. We hope that the topic of this Special Issue of Data will be of continued interest and we look forward to seeing progress in this field.